Pemanfaatan Kotoran Ternak Sebagai Energi Alternatif Dan Pupuk Untuk Mendukung Kebutuhan Perkebunan & Pertanian Di Desa Setiling - Cahyani, Aulia; Lauda, Lalu Dodi Nike; Afwa, Anastasya Auliya; Syari’ati, Zhilla Aulia; Nufus, Aan Cahyatul; Qolbi, Sulistia Zikrotul; Azkia, Hanipan; Huzaefa, Mohamad; Fajar, Iqbal Abdullah; Ikhsan, Bagus Rahman; Yanuartati, Baiq Yulfia Elsadewi (Universitas Mataram, 2025)
Setiling Village has abundant natural resource potential which can be utilized optimally by the local community, one of which is processing cow dung into biogas. Biogas, which is produced through anaerobic processing of organic materials, contains methane and carbon dioxide, and can be used as an alternative energy source. The Community Service Program (KKN) in Setiling Village aims to improve the quality of life of the community by utilizing local potential, especially in the fields of animal husbandry, agriculture and plantations. This program provides education about livestock waste management, including making simple biogas installations and developing biogas waste into Liquid Organic Fertilizer (POC). The results of the activity show that people can use biogas for household needs, while POC is used to increase agricultural and plantation productivity.